Passive energy-saving buildings realized by the combination of transparent heat-shielding glass and energy storage cement. (15th February 2023) - Chao, Luomeng; Sun, Changwei; Peng, Lihua; Li, Jiaxin; Sun, Miao; Bao, Lihong; Liu, Jia; Ma, Yonghong
Graphical abstract: Highlights: Developed an efficient energy-saving building model based on transparent heat-shielding glass and energy-storage cement. Halloysite nanotubes have been successfully used for energy storage cement. Transparent heat shielding glass and energy storage cement have a synergistic effect on building temperature regulation. The energy saving and economic payback period of the best scheme are 23.4% and 4.82 respectively. Abstract: Transparent heat-shielding (THS) glass based on selective absorbing materials has great application prospects in reducing building energy consumption. However, the heat generated by absorbing near-infrared light will also increase the indoor temperature, meanwhile, a single energy-saving material often causes obvious indoor temperature differences. This paper presents an energy-saving building room based on Csx WO3 @TiO2 coated glass (CG) and polyethylene glycol (PEG)/halloysite nanotubes (HNTs) energy storage cement (CP/F). The Csx WO3 (CWO) nanoparticles coating with TiO2 enhanced the stability of THS materials. The PEG/HNTs energy storage material exhibits a desirable phase change temperature of 28.70 °C, and relatively high latent heat of 74.84 J/g. The test room result shows that the combination of CG and CP/F can reduce the room temperature by about 10 °C, which is greater than the sum of CG and CP working alone owing to the synergistic effect of two materials, that is, CP/F can absorb part of the heat from CG. The combination of CG and CP/F made the indoor temperature distribution more uniform, with the maximum temperature difference decreasing from 6.7 °C to 3.1 °C. The annual energy saving of CP/F-CG in Changsha and Hong Kong is 14.7 % and 23.4 % respectively, and the economic payback period is 6.57 and 4.82 years respectively. The experimental results provide a new perspective on the development of energy-saving buildings.